2021
DOI: 10.1111/jcmm.16952
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from adipose‐derived mesenchymal stem cells alleviate liver ischaemia reperfusion injury subsequent to hepatectomy in rats by regulating mitochondrial dynamics and biogenesis

Abstract: Hepatic ischaemia reperfusion injury (HIRI) is a major factor leading to liver dysfunction after liver resection and liver transplantation. Adipose‐derived mesenchymal stem cells (ADSCs) have potential therapeutic effects on HIRI. Exosomes derived from ADSCs (ADSCs‐exo) have been widely studied as an alternative of ADSCs therapy. Thus, the aim of this study was to evaluate the potential protective effect and related mechanism of ADSCs‐exo on HIRI subsequent to hepatectomy. Rats were randomly divided into four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…However, ADSC-Exo administration inhibited pyroptosis. This is consistent with the results of previous studies that demonstrated the effect of ADSCs-Exo on liver injury [ 8 ]. It is well-known that pyroptosis is a kind of cell perforation and death that is caused by the accumulation and release of a large number of inflammatory factors by inflammatory cells.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, ADSC-Exo administration inhibited pyroptosis. This is consistent with the results of previous studies that demonstrated the effect of ADSCs-Exo on liver injury [ 8 ]. It is well-known that pyroptosis is a kind of cell perforation and death that is caused by the accumulation and release of a large number of inflammatory factors by inflammatory cells.…”
Section: Discussionsupporting
confidence: 93%
“…The ADSCs from passages 3 to 5 were cultured in a serum-free medium for 24 h, and the exosomes were obtained via differential centrifugation. As previously described, living cells, dead cells, cell debris, and large vesicles were removed from the supernatant through centrifugation at 300× g for 15 min, 2000× g for 25 min, and 10,000× g for 50 min, respectively [ 8 ]. The supernatant before centrifugation at 10,000× g was filtered through a 0.22 μm sterile filter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, they decreased DRP-1 and Fis-1 mRNA and protein expression related to mitochondrial fission. Additionally, exosomes significantly increase the expression of PGC-1α, NRF-1, and TFAM genes and proteins related to mitochondrial biogenesis ( 225 ). Another study in hindlimb ischemic animal models reported that MSC-derived extracellular vesicles activated VEGF receptors in endothelial cells, increased neovascularization at the site of ischemia, and accelerated recovery ( 226 ).…”
Section: Exosomes In Therapeuticsmentioning
confidence: 99%